2010
DOI: 10.1093/ndt/gfq689
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Pneumocystis jiroveci pneumonia (PcP) in renal transplant recipients

Abstract: Our case-control study reveals a novel risk profile for PcP. Renal transplant recipients with more pronounced renal insufficiency following rejection episodes and treated with intensified immunosuppression are at particular risk for PcP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
2
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(104 citation statements)
references
References 21 publications
3
91
2
8
Order By: Relevance
“…(15) insufficiency were associated with high risks of opportunistic infection, especially P. jirovecii pneumonia. (17) Our study, which also focused on severe bacterial pneumonia in RTRs, showed that renal function was a significant short-term mortality determinant in such patients.…”
Section: Discussionmentioning
confidence: 71%
“…(15) insufficiency were associated with high risks of opportunistic infection, especially P. jirovecii pneumonia. (17) Our study, which also focused on severe bacterial pneumonia in RTRs, showed that renal function was a significant short-term mortality determinant in such patients.…”
Section: Discussionmentioning
confidence: 71%
“…The PCP incidence in cancer patients without PCP prophylaxis varies by diagnosis (e.g., 22 to 45% for lymphomas and 25% for rhabdomyosarcomas) (125,264). Hematopoietic stem cell transplantation and solid organ transplantation also increases the risk of PCP, and these patients are generally offered PCP prophylaxis (72,75,106,325). Patients with collagen vascular disease have an elevated risk for PCP, particularly those with Wegener's granulomatosis (103,235).…”
Section: Recent Epidemiology Of Pcp In Non-hiv-infected Immunosuppresmentioning
confidence: 99%
“…The use of PCP chemoprophylaxis during CYC treatment is recommended by many experts (23,24) and should be considered with rituximab treatment as well. There are conflicting data about whether MMF may protect against or increase the risk of PCP in renal transplant recipients (25).…”
Section: Infectionsmentioning
confidence: 99%